Effectiveness of Social Media–Based Education and Demonstration on Parental Knowledge of Choking Mitigation and Management in Children - Satriani, Desy; Daud, Izma; Retno Wulan, Diah; Khalilati, Noor (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Choking in children presents a life-threatening emergency that requires parents to recognize risks and act promptly. If parents lack sufficient knowledge, they may respond too slowly, worsening outcomes. Objective: This study examined how social media–based health education and demonstration impact parental knowledge and cognitive preparedness to mitigate and manage choking incidents in children. Method: Researchers used a quantitative quasi-experimental design with a two-group pretest-posttest approach. The sample comprised 50 parents of children at Aisyiyah Bustanul Athfal 31 Kindergarten, Banjarmasin, divided into a social media education group and a demonstration education group. Result and Discussion: Researchers administered questionnaires before and after the interventions to collect data. Results showed that both the social media group (p < 0.001; r = 0.875) and the demonstration group (p < 0.001; r = 0.877) significantly improved parental knowledge and cognitive preparedness. Post-intervention outcomes for both groups remained comparable, revealing no statistically significant difference (p = 0.838). Conclusions: These findings show that both social media–based education and demonstration effectively enhance parental knowledge and cognitive preparedness for managing pediatric choking emergencies